The Challenge And Historical Education Model In The Millenial Era - Dr. I Made Pageh, M.Hum (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
History education is understood as rethinking education (reflective thinking). Nietzsche argued that history is only a kind of nostalgic shadow of people who have lost their self-confidence and living spirit (cf. Carr, 1972: 29). Therefore, history education is worth studied in millinal era, related to the information technology and industry 4.0 marked by cloud computers and automation industry. Futurelogists argue that history education would not fade away so that humans are not loosing the sense of humanity and a sense of time. To live, history education must be able to adapt to the zeitgeist and culture of the millennial era. If it does not, history education is just a curriculum burden. If history education can catch up the cloud computing tech and industry 4.0, it will be resourfull and can be communicated creatively and innovatively, through hybrid thinking of the past, present, and future. Historical learning in the millennial era must be equipped with data literacy skills for big data, cloud computing technology literacy, and humanitarian literacy. Humanitarian literacy, nationality, local wisdom can be packaged as part of the world through hybridization in glocalization. Historical learning must immediately reorient to the future such as the era of cloud computing and industry 4.0.